The Tendency of Hopelessness in Final Students: The Role of Tawakal and Peer Attachment as Muslim Students - Citamia Vastya Ihsani; Deden Sudirman; Zulmi Ramdani; Ahmad Fahmi Dinulloh (Jurnal Psikologi Islam dan Budaya, 2024)
When they are at the final level of completing their studies, there are many conditions that make students feel hopeless. However, as Muslims, there are many conditions that enable students to survive this despair. The aim of this research is to look at the role of trust and peer attachment as predictors of hopelessness in final year Muslim students. A quantitative research design was used involving 375 Muslim students who were at the final level of college. Multiple regression data analysis was tested on the proposed hypothesis with significance results below 5%. This means that there is an influence of trust and peer attachment on hopelessness in final year Muslim students. This study has implications for strengthening trust in Allah and strengthening positive relationships with peers as one of the best ways to avoid situations of hopelessness when working on final assignments.